Endovascular reperfusion of M2 occlusions in acute ischemic stroke reduced disability and mortality: ETIS Registry results. (27th May 2021) - Muszynski, Patricio; Anadani, Mohammad; Richard, Sébastien; Marnat, Gaultier; Bourcier, Romain; Sibon, Igor; Dargazanli, Cyril; Arquizan, Caroline; Maïer, Benjamin; Blanc, Raphaël; Lapergue, Bertrand; Consoli, Arturo; et al.
Abstract : Background: The predictors of successful reperfusion and the effect of reperfusion after endovascular treatment (EVT) for M2 occlusions have not been well studied. We aimed to identify predictors of successful reperfusion and the effect of reperfusion on outcomes of EVT for M2 occlusions in current practice. Methods: Patients with acute ischemic stroke due to isolated M2 occlusions who were enrolled in the prospective multicenter Endovascular Treatment in Ischemic Stroke (ETIS) Registry in France between January 2015 and March 2020 were included. The primary outcome was a favorable outcome, defined as modified Rankin Scale (mRS) score of 0–2 at 90 days. Successful reperfusion was defined as an improvement of ≥1 points in the modified Thrombolysis In Cerebral Infarction score between the first and the last intracranial angiogram. Results: A total of 458 patients were included (median National Institutes of Health Stroke Scale (NIHSS) score 14; 61.4% received prior intravenous thrombolysis). Compared with the non-reperfused patients, reperfused patients had an increased rate of excellent outcome (OR 2.3, 95% CI 0.98 to 5.36; p=0.053), favorable outcome (OR 2.79, 95% CI 1.31 to 5.93; p=0.007), and reduced 90-day mortality (OR 0.39, 95% CI 0.19 to 0.79; p<0.01). Admission NIHSS score was the only predictor of successful reperfusion. First-line strategy was not a predictor of successful reperfusion or favorable outcome, but the use of a stent retriever, alone or with an aspiration catheter, was associated with higher rates of procedural complications and 90-day mortality. Conclusions: Successful reperfusion of M2 occlusions reduced disability and mortality. However, safety is a concern, especially if the procedure failed.